Common variant in OXTR predicts growth in positive emotions from loving-kindness training. (November 2016) - Isgett, Suzannah F.; Algoe, Sara B.; Boulton, Aaron J.; Way, Baldwin M.; Fredrickson, Barbara L.
Highlights: OT genetic variability predicts positive emotions for socially-focused meditation training. OXTR rs1042778 predicted growth in daily positive emotions over 6 weeks. OXTR rs1042778 GG individuals increased in positive emotions during a socially-focused meditation training. OXTR rs1042778 T-carriers and GG individuals did not increase in positive emotions during non-social meditation training. Abstract: Ample research suggests that social connection reliably generates positive emotions. Oxytocin, a neuropeptide implicated in social cognition and behavior, is one biological mechanism that may influence an individual's capacity to extract positive emotions from social contexts. Because variation in certain genes may indicate underlying neurobiological differences, we tested whether several SNPs in two genes related to oxytocin signaling would show effects on positive emotions that were context-specific, depending on sociality. For six weeks, a sample of mid-life adults ( N = 122) participated in either socially-focused loving-kindness training or mindfulness training. During this timespan they reported their positive emotions daily. Five SNPs within OXTR and CD38 were assayed, and each was tested for its individual effect on daily emotions. The hypothesized three-way interaction between time, training type, and genetic variability emerged: Individuals homozygous for the G allele of OXTR rs1042778 experienced gains in daily positive emotions from loving-kindness training, whereas individuals with the T allele did not experience gains in positive emotions with either training. These findings are among the first to show how genetic differences in oxytocin signaling may influence an individual's capacity to experience positive emotions as a result of a socially-focused intervention.